Review of Physiological Aspects of Erythropoie sis: A Narrative Literature Review - Hedayanti, Noor; Wahyudi, Arif (Sriwijaya Journal of Internal Medicine, 2023)
Erythropoiesis is the development of red blood cells. Within the confines of the bone marrow, erythroid progenitor cells proliferate and differentiate into large nucleated proerythroblasts, which are committed to producing cells of the erythroid series. Th is literature review aimed to describe the physiology of erythropoiesis and its application in medical science. All stages of erythroid development are ref erred to as the erythron. Proerythroblasts, which possess ribosomes and can produce proteins, differentiate through several forms between erythroblasts while synthesizing hemoglobin and progressively removing most of th e intracellular structures, including the nucleus. Thus the mature erythroblast becomes more compact and progressively takes on the shape and character istics of the erythrocyte. Hemoglobin is easily seen, and its amount increases as the size of the nucleus decreases during the basophilic and polychromatophilic stages. The orthochromatic erythroblast (normoblast) is the smallest of the nucleated erythrocyte precursors.